Retrospective Analysis of Contrast-enhanced Ultrasonography Effectiveness in Reducing Time to Diagnosis and Imaging-related Expenditures at a Single Large United States County Hospital. Issue 2 (June 2019) - Streb, Jeffrey W.; Tchelepi, Hisham; Malhi, Harshawn; Deurdulian, Corinne; Grant, Edward G.
Abstract : Abstract: Hepatic and renal lesions detected during ultrasound examinations frequently require subsequent contrast-enhanced computed tomography (CT) or magnetic resonance imaging (MRI) for characterization, delaying time to imaging diagnosis and increasing overall health care expenditures. Contrast-enhanced ultrasonography (CEUS) is a comparatively low-cost diagnostic tool that is underutilized in the evaluation of such indeterminate or suspicious hepatic and renal lesions. A retrospective chart review of CEUS examinations performed in our department demonstrated significantly shorter time to imaging diagnosis with CEUS compared to CT or MRI, largely due to the ability to perform the CEUS examination at the time of initial examination. For example mean time to completion for outpatient examinations was 5.2, 52.3, and 123.5 days for CEUS, CT, and MRI, respectively. The majority (78.4%) of CEUS examinations were completed the same day as the initial examination. Additionally, 66.7% of CEUS examinations were deemed diagnostic, abrogating further workup with CT or MRI in most cases. Annual imaging cost reduction of up to US 117, 000 is anticipated in our institution based on projected reductions in follow-up CT and MRI examinations. These results indicate when CEUS was used as a first step to characterize both incidental lesions in patients without known risk factors for malignancy as well as suspicious lesions in patients with risk factors it can greatly reduce time to diagnosis and health care expenditures.